PENGGUNAAN MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN IPS DI KELAS VI SDN 24 PONTIANAK TENGGARA - Etty Hayati (Universitas Tanjungpura, 2020)
AbstractStudent learning outcomes of class VI A SDN 24 South East Pontianak shows 11 of 23 students do not reach the minimum completeness criteria. So that a study aimed to find out the improvement of student learning outcomes in social studies subjects in class VI A SDN 24 South East Pontianak through the use of learning models make a match. This research was conducted in two cycles and used two instruments, namely: observation sheet and written test form in the form of filling. The results of Cycle I showed the ability to prepare RPP is 77.94, and the average teacher's skills in applying make a match is 83.33. In Cycle I the pre-test scores showed 12 students had reached the minimum completeness criteria, while the post-test scores showed 23 students had reached the minimum completeness criteria (100%) with an average of 82.39. The results of Cycle II showed that the RPP preparation got a value of 92.64 and the use of make a match skill was 92.64. In Cycle II the results of the post-test showed that the remaining 23 (100%) had reached the minimum completeness criteria with an average of 92.17. Keywords: Classroom action research, Model Make a Match, Social Sciences Subjects, Student Learning Outcomes